The Chain Rule - Exercise 1


Exercise 1. Find the derivative of

\begin{displaymath}f(t) = \left(t^2 - \frac{2}{t^3} \right)^2\;.\end{displaymath}

Answer. We will use the Chain rule. Set

\begin{displaymath}u = t^2 - \frac{2}{t^3}\;\;\mbox{and}\;\; y = f(t)\;.\end{displaymath}

Then we have y = u2. The Chain rule implies

\begin{displaymath}\frac{dy}{dt} = \frac{du}{dt} \frac{dy}{du}\;.\end{displaymath}

Since

\begin{displaymath}\frac{du}{dt} = 2t + \frac{6}{t^4}\;\;\mbox{and}\;\; \frac{dy}{du} = 2u\end{displaymath}

we get

\begin{displaymath}\frac{dy}{dt} = \left(2t + \frac{6}{t^4} \right) 2u = 2 \left...
...+
\frac{6}{t^4} \right) \left(t^2 - \frac{2}{t^3} \right) \cdot\end{displaymath}


[Back] [Next]
[Trigonometry] [Calculus]
[Geometry] [Algebra] [Differential Equations]
[Complex Variables] [Matrix Algebra]

S.O.S MATHematics home page

Do you need more help? Please post your question on our S.O.S. Mathematics CyberBoard.


Mohamed A. Khamsi

Copyright 1999-2017 MathMedics, LLC. All rights reserved.
Contact us
Math Medics, LLC. - P.O. Box 12395 - El Paso TX 79913 - USA
users online during the last hour